Catalytic transformation of 2, 5-furandicarboxylic acid to adipic acid over niobic acid-supported Pt nanoparticles. Issue 55 (21st June 2019) - Wei, Longfu; Zhang, Junxian; Deng, Weiping; Xie, Shunji; Zhang, Qinghong; Wang, Ye
Abstract : Biomass-derived 2, 5-furandicarboxylic acid was successfully converted to adipic acid over a niobic acid-supported Pt catalyst in water under H2 . Abstract : The conversion of biomass-derived molecules into adipic acid represents a highly attractive green route for sustainable production of adipic acid, a key monomer of nylon 66 and polyurethane. Here, we report the direct synthesis of adipic acid from 2, 5-furandicarboxylic acid, which can be obtained from cellulose-based 5-hydroxymethylfurfural, using a niobic acid-supported platinum catalyst under hydrogen in water.